Design of a multiple-input parallel SC DC-DC converter and its efficiencyestimation method - Eguchi, Kei; Sugimura, Tatsuya; Pongswatd, Sawai; Tirasesth, Kitti; Sasaki, Hirofumi (My University, 2009)
A multiple-input parallel SC (Switched Capacitor) DC-DC converter and itsefficiency estimation method are proposed in this paper. The proposed parallelconverter consists of two different kinds of converter blocks: 1. a 1.5×step-up SC DC-DC converter employing an input voltage from a lithium battery and2. a novel step-up converter employing an input voltage from clean energysupplies. Since the proposed step-up converter can achieve not only a largestep-up conversion ratio but also a wide input range, the proposed parallelconverter enables us to extend battery runtime, reduction of heat, and so on.Furthermore, concerning the proposed converter, theoretical analyses areperformed to estimate power efficiency. The proposed analysis technique can beextended to the circuit design of other SC DC-DC converters. The validity ofcircuit design and theoretical formulas is confirmed by SPICE simulations.ICIC International © 2009.
Keywords: Charge-pump circuits; Clean energy; Multiple input circuits; Parallel converters; Power converters; Switched-capacitor circuits